ODDS & ENDS. (Quill, 2003)
Presents news briefs related to freedom of information in the U.S. as of September 2003. Settlement of a lawsuit between Arkansas Governor Mike Huckabee and the Arkansas Educational Television Network in July; Dismissal of a lawsuit against Vanette Webb, former school board member in Escambia County, Florida, in July; Decline in the amount of media coverage of the federal government.